PERENCANAAN PEMBELAJARAN OLEH GURU DI SMP NEGERI 23 PADANG DALAM SETTING INKLUSI - Gallan Berkah Mahesa, Damri, Yosfan Azwandi (Universitas Negeri Padang, 2013)
The research was background by the low minimum completeness criteria are achieved by special needs child (ABKh) in state junior high school 23 Padang (inclusive-setting) in infield of biology. Researcher limit the problems on how study plans was planned in learning biology by teacher state junior high school 23 Padang in modifying the study plans for ABKh. research purposes to get an idea of ​​the shape, obstacles, and the efforts of teachers to modify study plans for ABKh. Researchers as key informants with purposive sampling. Technique data collecting was performed by interviews, observation, and documentation. Data analysis was performed during the study. The planning of learning outcomes acquired compiled yet accommodate ABKh.